Transient inhibition of cell division in competent pneumococcal cells results from deceleration of the septal peptidoglycan complex - Dimitri Juillot; Cyrille Billaudeau; Isabelle Mortier-Barrière; Aurélien Barbotin; Armand Lablaine; Patrice Polard; Nathalie Campo; Rut Carballido-López (Nature Communications)
Abstract Membrane protein ComM transiently inhibits cell division during the development of the competence state in the pathogenic bacterium Streptococcus pneumoniae, but the underlying molecular mechanisms remain unclear. Here we show that, in competent cells, ComM moves together with, and reduces the speed of, septal peptidoglycan synthetic complex FtsW:PBP2x. ComM directly interacts with the putative FtsW:PBP2x activator DivIB, and overproduction of DivIB counteracts FtsW:PBP2x deceleration along the cell division delay in competent cells. Our results support a model in which ComM reduces septal peptidoglycan synthesis by interfering with DivIB activity during competence in S. pneumoniae.